Digital Literacies Learning Needs in Rural Ontario Elementary Schools: Teacher Insights - Schira Hagerman, Michelle; Neisary, Sima (Canadian Journal of Education / Revue canadienne de l'éducation, 2024)
Despite known inequalities of digital access in rural Canada, we know little about the foundational digital literacies learning needs of students attending rural elementary schools. This exploratory case study, conducted in Ontario, presents 13 rural-serving Grade 4–6 teachers’ insights on the access needs and digital literacies learning needs of their students. Results point to a set of mixed digital materialities and opportunities across home and school that raise concerns of digital marginalization for children who are least connected. Teachers named 14 unique digital literacies learning needs in relation to online reading, digital writing, and participation. Their insights also reflect an understanding of digital literacies learning as situated in a complex assemblage of structural, social, emotional, cultural, cognitive, developmental, technological, and material considerations. Implications for policy and the design of uniquely rural solutions to digital literacies instruction are discussed.